Editorial - Mercer, Sarah; Ryan, Stephen (Studies in Second Language Learning and Teaching, 2015)
The various papers that make up this special issue of Studies in Second Language Learning and Teaching have emerged from the first Psychology in Language Learning (PLL) conference, which took place in May 2014 at the University of Graz, Austria. We would like to open this special issue—the first of a series of two—by discussing that conference’s background, its focus, and its possible future in the hope that such a discussion will clarify our current aims and scope in this special issue. The original impetus for organising the conference came from a book that we, the editors of this special issue, were privileged to edit (Mercer, Ryan, & Williams, 2012). The rationale behind that book was to bring together different areas of language learning psychology within a single volume. The experience of working on the book in conjunction with so many distinguished scholars from around the world convinced us of the potential of an approach that emphasises the commonality between various strands of research that had previously been developing in isolation from each other. Many subareas of our field, such as motivation, autonomy, self, identity, strategy use, and beliefs, have existed as separate communities, with little exploration of the interplay and connections between these closely related areas. Our aim in organising the 2014 conference was to build on the momentum of the book by creating a shared space that would facilitate exchange, and providing opportunities to explore and expand upon how these different areas are interlinked. A secondary aim was to reinterpret the word psychology within the context of foreign language education. For so long, psychology has been closely associated with cognitive processes in second language acquisition and with psycholinguistics, but in our book, the conference, and in this special issue, we are seeking to specifically foreground social and educational psychology themes. Language learning is primarily a social and educational activity and we feel that these dimensions also need to be reflected in how we frame discussions of the psychology of learning a second or foreign language.